Logan Medallist 4. Large-Scale Impact and Earth History - Grieve, Richard (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2017)
The current record of large-scale impact on Earth consists of close to 200 impact structures and some 30 impact events recorded in the stratigraphic record, only some of which are related to known structures. It is a preservation sample of a much larger production population, with the impact rate on Earth being higher than that of the moon. This is due to the Earth's larger physical and gravitational cross-sections, with respect to asteroidal and cometary bodies entering the inner solar system. While terrestrial impact structures have been studied as the only source of ground-truth data on impact as a planetary process, it is becoming increasingly acknowledged that large-scale impact has had its effects on the geologic history of the Earth, itself. As extremely high energy events, impacts redistribute, disrupt and reprocess target lithologies, resulting in topographic, structural and thermal anomalies in the upper crust. This has resulted in many impact structures being the source of natural resources, including some world-class examples, such as gold and uranium at Vredefort, South Africa, Ni–Cu–PGE sulphides at Sudbury, Canada and hydrocarbons from the Campeche Bank, Mexico. Large-scale impact also has the potential to disrupt the terrestrial biosphere. The most devastating known example is the evidence for the role of impact in the Cretaceous–Paleocene (K–Pg) mass extinction event and the formation of the Chicxulub structure, Mexico. It also likely had a role in other, less dramatic, climatic excursions, such as the Paleocene–Eocene–Thermal Maximum (PETM) event. The impact rate was much higher in early Earth history and, while based on reasoned speculation, it is argued that the early surface of the Hadean Earth was replete with massive impact melt pools, in place of the large multiring basins that formed on the lower gravity moon in the same time-period. These melt pools would differentiate to form more felsic upper lithologies and, thus, are a potential source for Hadean-aged zircons, without invoking more modern geodynamic scenarios. The Earth-moon system is unique in the inner solar system and currently the best working hypothesis for its origin is a planetary-scale impact with the proto-Earth, after core formation at ca. 4.43 Ga. Future large-scale impact is a low probability event but with high consequences and has the potential to create a natural disaster of proportions unequalled by other geologic processes and threaten the extended future of human civilization, itself.